2012
DOI: 10.1038/ncomms1749
|View full text |Cite
|
Sign up to set email alerts
|

Transient activation of specific neurons in mice by selective expression of the capsaicin receptor

Abstract: The ability to control the electrical activity of a neuronal subtype is a valuable tool in deciphering the role of discreet cell populations in complex neural circuits. Recent techniques that allow remote control of neurons are either labor intensive and invasive or indirectly coupled to neural electrical potential with low temporal resolution. Here we show the rapid, reversible and direct activation of genetically identified neuronal subpopulations by generating two inducible transgenic mouse models. Confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 51 publications
2
63
0
Order By: Relevance
“…We performed a series of control experiments to confirm that expression of Trpv1 was restricted to Agrp neurons in the arcuate nucleus and not in off-target cells ( Figure S1 and Experimental Procedures). Trpv1 is a cation channel that is activated by the exogenous agonist capsaicin (Caterina et al, 1997) in a rapid and reversible manner (Güler et al, 2012). Slice whole-cell recordings showed that capsaicin increased the firing rate of Agrp neurons ( Figure 2C).…”
Section: Acute Agrp Neuronal Activationmentioning
confidence: 95%
See 1 more Smart Citation
“…We performed a series of control experiments to confirm that expression of Trpv1 was restricted to Agrp neurons in the arcuate nucleus and not in off-target cells ( Figure S1 and Experimental Procedures). Trpv1 is a cation channel that is activated by the exogenous agonist capsaicin (Caterina et al, 1997) in a rapid and reversible manner (Güler et al, 2012). Slice whole-cell recordings showed that capsaicin increased the firing rate of Agrp neurons ( Figure 2C).…”
Section: Acute Agrp Neuronal Activationmentioning
confidence: 95%
“…On the other hand, DREADD can be used to activate Agrp neurons by peripherally injecting receptor-ligand with robust induction of food intake (Krashes et al, 2011) but with more coarse kinetics . We used transgenic mice that conditionally express Trpv1 in Cre-expressing cells (Arenkiel et al, 2008;Güler et al, 2012) (R26-LSL-Trpv1; Figure 2B) to selectively introduce Trpv1 in Agrp neurons. By backcrossing these mice (R26-LSL-Trpv1) to a Trpv1 knockout background and then to Agrp-Cre mice, we generated animals that express Trpv1 exclusively in the Agrp neurons (hereafter, Agrp-Trpv1 mice; Figures 2B and S1).…”
Section: Acute Agrp Neuronal Activationmentioning
confidence: 99%
“…AgRP DTR mice were put on a genetic background in which activation of dopamine neurons is mediated through the restricted expression of Trpv1, the capsaicin-receptor, in dopamine neurons; referred to as AgRP DTR ; DAT TRPV1 mice, see Figure 3A (Guler et al, 2012). Adult AgRP DTR ; DAT TRPV1 mice were presented with a palatable high-fat diet and the consequence of AgRP neuron ablation was evaluated in the presence or absence of capsaicin in the drinking water ( Figure 3C,3D).…”
Section: Feeding Relies On Food Palatability and Dopamine Tone When Amentioning
confidence: 99%
“…(See also Figure S2). (Guler et al, 2012)) were crossed to Agrp DTR/+ mice (Luquet et al, 2005) on the C57Bl/6 background to generate AgRP DTR .…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…(Simone et al 1998). CAP may be transported via the blood-brain barrier (BBB), although the mechanism of the transport is not known (Güler et al 2012).…”
Section: Introductionmentioning
confidence: 99%